A Comparison of Bubbles in Mixed Alginate Impression Materials between Alginate and Artificial Alginate Practicing Groups - Aerarunchot, Suwadee; Anussornrajakit, Anuratchanee; Ponsri, Saranya; Lorsuwansiri , Patlapa; Pitiphat, Waranuch (Khon Kaen University Dental Journal, 2021)
A novel, inexpensive, material has been developed from diatomaceous earth and glutinous rice starch as an alternative to dental alginate to aid students in practice of alginate hand mixing. This study aimed to compare the performance of students who practiced with alginate to those practiced with artificial alginate in regards to air bubble formation on surface of alginate samples. Study participants included 40 first year dental students at the Faculty of Dentistry, Khon Kaen University who never practiced alginate mixing previously. All participants received information about alginate mixing via video instruction media. They were then randomly assigned into 2 groups with 20 participants each: alginate practicing group and artificial alginate practicing group. Surface air bubble formation in alginate samples was measured before and after practice for each participant. Differences between two groups were compared using Mann-Whitney U test, Shapiro-Wilk testing show non-normal distribution of data then non-parametric statistic was required to compare median instead. Mean of difference in group 1 is 5.3 mm2 and interquartile range is -2.0 to 15.9 mm2, Median of difference in group 2 is 5.5 mm2 and interquartile range is -3.9 to 19.5 mm2. Mann-Whitney U test show that median of difference in before and after practice of bubbles area on surface of alginate sample between group 1 and group 2 were no significant differences (p=0.96). The findings suggest that there is no difference in alginate mixing performance between students who practiced with alginate and those who practiced with artificial alginate.